CB(1) antagonism restores hepatic insulin sensitivity without normalization of adiposity in diet-induced obese dogs - Kim, Stella P. (American Physiological Society, 2012)
The endocannabinoid system is highly implicated in the development of insulin resistance associated with obesity. It has been shown that antagonism of the CB(1) receptor improves insulin sensitivity (S(I)). However, it is unknown whether this improvement is due to the direct effect of CB(1) blockade on peripheral tissues or secondary to decreased fat mass. Here, we examine in the canine dog model the longitudinal changes in S(I) and fat deposition when obesity was induced with a high-fat diet (HFD) and animals were treated with the CB(1) antagonist rimonabant. S(I) was assessed (n = 20) in animals fed a HFD for 6 wk to establish obesity. Thereafter, while HFD was continued for 16 additional weeks, animals were divided into two groups: rimonabant (1.25 mg·kg(−1)·day(−1) RIM; n = 11) and placebo (n = 9). Euglycemic hyperinsulinemic clamps were performed to evaluate changes in insulin resistance and glucose turnover before HFD (week −6) after HFD but before treatment (week 0) and at weeks 2, 6, 12, and 16 of treatment (or placebo) + HFD. Magnetic resonance imaging was performed to determine adiposity- related changes in S(I). Animals developed significant insulin resistance and increased visceral and subcutaneous adiposity after 6 wk of HFD. Treatment with RIM resulted in a modest decrease in total trunk fat with relatively little change in peripheral glucose uptake. However, there was significant improvement in hepatic insulin resistance after only 2 wk of RIM treatment with a concomitant increase in plasma adiponectin levels; both were maintained for the duration of the RIM treatment. CB(1) receptor antagonism appears to have a direct effect on hepatic insulin sensitivity that may be mediated by adiponectin and independent of pronounced reductions in body fat. However, the relatively modest effect on peripheral insulin sensitivity suggests that significant improvements may be secondary to reduced fat mass.